A nomogram diagnostic cardiovascular disease in patients with erythrodermic psoriasis in Chinese - Zou, Yue-Min; Zhou, Dong-Mei; Wu, Man-Ning; Zhao, Xin-Yuan (Frontiers in Immunology, 2023)
Objective: Patients with erythrodermic psoriasis (EP) are associated with an increased risk of cardiovascular disease (CVD), because of the more severe inflammation in the skin areas. This study aimed to develop a diagnostic model for the risk of CVD in EP patients based on the available features and multidimensional clinical data. Methods: A total of 298 EP patients from Beijing Hospital of Traditional Chinese Medicine were retrospectively included in this study from May 5th, 2008, to March 3rd, 2022. Of them, 213 patients were selected as the development set by random sampling, and clinical parameters were analyzed by univariate and backward stepwise regression. Whereas the remaining 85 patients were randomly selected as the validation set. The model performance was later assessed in terms of discrimination, calibration, and clinical usefulness. Results: In the development set, the CVD rate was 9%, which was independently correlated with age, glycated albumin (GA>17%), smoking, albumin (ALB<40 g/L), and lipoprotein(a) (Lp(a)>300 mg/L). The area under the ROC curve (AUC) value was 0.83 (95% confidence interval CI, 0.73,0.93). For the validation set of EP patients, the AUC value was 0.85 (95%CI, 0.76,0.94). According to decision curve analysis, our model exhibited favorable clinical applicability. Conclusion: EP patients with age, GA>17%, smoking, ALB<40 g/L, and Lp(a)>300 mg/L are associated with a higher risk of CVD. The nomogram model performs well in predicting the probability of CVD in EP patients, which may help improve perioperative strategies and good treatment outcomes.